2018
DOI: 10.5860/crl.79.4.499
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Research Mindset and Information-Seeking Behaviors of Undergraduate Music Students

Abstract: This article examines the mindset and process of undergraduate music majors conducting research in their discipline. While working with students in a writing-intensive music history class, the authors conducted several surveys, focus groups, and task-based assessments. Results indicated that most were overconfident in their research abilities, lacked experience with the research process, and struggled to locate and properly cite scholarly sources. Based on existing literature, music students exhibited research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…A number of studies have looked at library users’ information behavior in order to evaluate LUE programs. A recent study by Clark and Johnstone (2018) of Music undergraduate students found that, although many of the students expressed that they prioritized library materials in their research, they did not perform adequately in the research task assessment. Further, the students preferred online resources and friends to professors and librarians.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A number of studies have looked at library users’ information behavior in order to evaluate LUE programs. A recent study by Clark and Johnstone (2018) of Music undergraduate students found that, although many of the students expressed that they prioritized library materials in their research, they did not perform adequately in the research task assessment. Further, the students preferred online resources and friends to professors and librarians.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In STEM education, while the phrase information literacy itself has not gained traction, there are a variety of terms used to identify the concept of information finding and dissemination, that include science communication, data information literacy, science media education, STEM literacy for learning, and critical appraisal (Clark and Johnstone 2018;Kennedy, Cole, and Carter 1999;Phelps, Hyde, and Wolf 2018). The ability to find, use, disseminate and share scientific information is important both professionally for undergraduate stem students both in their academic, and personal lives.…”
Section: Literature Reviewmentioning
confidence: 99%
“…8 Other research shows that many students are overconfident in their search skills; in reality, they struggle to find proper resources. 9 They also lack research-related search skills such as checking documents from nonacademic resources or using important figures to identify and select relevant documents. 10 These difficulties may arise because students are familiar with ordinary information searches but lack the specific skills and knowledge needed for scholarly search.…”
Section: Introductionmentioning
confidence: 99%